Buenaventura y el circuito comercial del Valle del Cauca, 1885-1900 (2017)
"The commercial circuit developed in the Valle del Cauca at the end of the 19th century was a complex and diverse process, which integrated the action of multiple agents in different places. This thesis analyses those ones that intervened directly in the commercial activity: merchandise, merchants, means of transportation and Buenaventura?s customs over a wide commercial space, covering the valley of Cauca's river to Europe and United States ports. The sources come mainly from Buenaventura's custom files, and consider the value and weight of the traded goods, the taxes and the amount of ships that entered and left the port. From these, some others aspects arise that have to do with the merchant's network that moved from the region of Cali-Buenaventura, the transport system articulation, the smuggling control and the merchantsociety." -- Tomado del Formato de Documento de Grado.